Dinamika perpustakaan SMP Negeri 12 Bandung: motivasi pustakawan, kendala operasional, dan solusi strategis - Wanda Nadriah Fajrianti Rabbah; Linda Setiawati; Lutfi Khoerunnisa (Libraria: Jurnal Ilmu Perpustakaan dan Informasi, 2025)
School libraries are key elements in supporting literacy and education ecosystems, but their success depends on the dynamics of librarian motivation, operational barriers, and strategic solutions. This study aims to identify librarian motivation factors, analyze operational challenges, and formulate strategic solutions at the SMP Negeri 12 Bandung Library. A qualitative approach was used by collecting data through in-depth interviews with the head of the library and physical observation of library activities and facilities on March 12, 2025. The results showed that librarian motivation was driven by consistent A accreditation status and collaboration with student interns, although hampered by minimal professional training. Operational challenges include low student reading interest (only 30% visit regularly), collections dominated by textbooks (60%), and limited infrastructure, such as a 60 m² space for 5,000 books. Strategic solutions such as creative literacy programs in the form of book trailer competitions, collaboration with publishers, and space revitalization plans increased collection interaction by 15% and service awareness by 20%. In conclusion, the adoption of technologies such as e-libraries and digital literacy training can make school libraries dynamic learning centers, addressing operational limitations and student needs in the digital era.